FUNCTIONAL FEATURES OF THE SOCIALLY MARKED VOCABULARY (ON THE MATERIAL OF THE ITALIAN LANGUAGE) - Bumar , Kristina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
This paper analyzes the processes of the progression of particular social vocabularies. The definition of advanced concepts has been considered in the analysis, and their functional features of the terms of socially marked vocabulary have been revealed as well. We attempted to distinguish and compare such notions as jargon, dialect, argot, vernacular and cant among the concept of general conversation. The characteristic features that are inherent to one or another sociolect are investigated. Socially marked vocabulary reflects important moments of human communicative behavior in a society, which is a part of national culture. In the modern world, where the globalization of cultures in conversation is observed, the vocabulary ceases to be confined to one particular language but becomes the property of a social stratum of a particular social group. In the analysis, in general, it became clear that in the Italian language there are only four varieties of the social dialect – dialect, jargon, vernacular and argot (But you have four here). The article reveals that the units of the vocabularies have their negative influence, since, in our study, the conversation has historically been formed in the criminal environment and socially low strata of the population. The operation of the overwhelming majority of units goes beyond the limits of a particular social group and becomes a colloquial language and is often used by writers in Italian literary works. Additionally, the examples presented in the article show that the Italians are trying to comprehend the essence of these concepts and distinguish them from each other. In some cases, in different social groups, we conclude that the vocabularies are implemented at the lexical-semantic, pragmatic, phonological, conceptual and contextual levels, enrich the content of the literary language, and get into and enrich literary language. It is hoped this study will inform practitioners and theorist about socially marked vocabulary used. _________________ References • Arapov, M. V. Otkuda slovo fenya? (Leningrad, Russkaya rech, 1969): 117–119. • Galperin, I. R. Ocherki po stilistike anglijskogo yazyka (Moskva, Izdatelstvo literatury na inostrannyh yazykah, 1958), 462. • Grachev, M. A. Slovar tysyacheletnego russkogo argo (Moskva, Ripol Klassik, 2003), 1119. • Enciklopediya Suchasnoyi Ukrayini (2007), dostup http://esu.com.ua/search_articles.php?id=24450. • Murashov, A. A. Kultura rechi uchitelya (Moskva, Moskovskij psihologo-socialnyj institut, 2002), 432. • «Rozmovna mova.» Izbornik (2001), dostup http://litopys.org.ua/. • «Argo.» Enciclopedia Britannica (2019), access https://www.britannica.com/. • «Argot.» Vocabulary.com Dictionary (2019), access https://www.vocabulary.com/ dictionary/argot. • Biber, D. Longman Grammar of Spoken and Written English (Harlow, Pearson Education Limited., 1999), 1203. • Cambridge Dictionary (2019), access https://dictionary.cambridge.org/. • Dctionary.com (2019), access https://www.dictionary.com/ • Halliday, M. A. Il linguaggio come semiotica sociale. Un’interpretazione sociale del linguaggio e del significato (Bologna, Zanichelli, 1983), 63. • Kirk, J., Ó Baoill, D. Travellers and their Language (Belfast, Queen’s University Belfas, 2002), 196. • «Jargon.» The American Heritage Dictionary (2019), access https://ahdictionary.com/word/search.html?q=jargon. • Odell, L., Vacca, R., Hobbs, R. Elements of language: Fifth course (teacher’s edition) (New York, Holt Rinehart & Winston; Teachers Guide edition, 2007), 1126. • Peterson, B. «The Linguistics of LOL.» Washingtonian (2014). • Šipka, D. Phonologiacal and semantic markers in the substandart lexicon (Poznan, Adam Mickievicz University, 2001): 187–194. • «Treccani.» Enciclopedia dell’Italiano (2019), access http://www.treccani.it/ vocabolario/. • «Vernacular and standard language.» Mahasaraswati Denpasar University (2014), access https://dayupurnami.wordpress.com/vernacular-and-standard-language/.